PEMBENTUKAN FREE TRADE AREA ANTARA KOREA SELATAN DAN UNI EROPA - Husnil Ma'sum (HI 16 UMY 043, 2016)
*43 Trade liberalization is a policy to reduce and eliminate trade barriers in an effort to improve the flow of goods and services. Trading conducted by South Korea and the European Union each year has increased. South Korea and the EU form a Free Trade Area with the aim of achieving their respective interests. Free Trade Area into the South Korean economy atay strategy in expanding its "Global Korea" in various fields which will boost the domestic economy. In addition, the EU is also making South Korea the first country in Asia to cooperate Free Trade Area with the EU which will be awala EU expand cooperation in Asia or the so-called "Global Europe"